Effects of NH4+-N: NO3−-N ratio on growth, nutrient uptake and production of blueberry (Vaccinium spp.) under soilless culture - Anwar, Ali; Zheng, Junming; Chen, Chunfeng; Chen, Mengqing; Xue, Yanxu; Wang, Jinmiao; Su, Wei; Chen, Riyuan; Song, Shiwei (Frontiers in Plant Science, 2024)
Blueberry (Vaccinium corymbosum) is a small pulp shrub, which prefers to grow on a soilless culture. For soilless culture, nutritional management remains typically vital for blueberry production. However, the effect of different nutritional treatments on blueberry growth and production is largely unknown. This study was designed to investigate to formulate a specific nutritional treatment for blueberry. The results showed that NH4+-N: NO3−-N ratios significantly affected the growth, nutrient uptake, physiological characteristics, and flowering, as well as the fruiting characteristics of blueberry plants. The number of shoots and top projection area was increased considerably by 25:75 treatment. In contrast, 50:50 treatment promotes plant height, shoot length, and stem thickness, increasing chlorophyll contents, photosynthetic capacity, and P, Ca, and Mg in leaves. In contrast, 50:50 treatment promotes the flowering fruiting rate and prolongs the blueberry flowering period. The maximum soluble sugar contents were noted in 25:75, while maximum starch contents were reported in the 50:50 treatment. The treatments 100:0 and 75:25 promote early flowering and accelerate fruit set. Notably, NH4+-N: NO3−-N ratios; 50:50 treatment significantly encourages plant growth, nutrient uptake, chlorophyll contents, photosynthetic capacity, and fruit setting rate in blueberry plants. These findings suggested that NH4+-N: NO3−-N ratios 50:50 is the most appropriate treatment that significantly promotes vegetative growth and enhances production in blueberry plants. This study provides valuable information for improved blueberry production under a controlled environment.